A symbolic calculus and a parametrix construction for pseudodifferential operators with non-smooth negative definite symbols - Alexander Potrykus (Rev. Mat. Complut., 2009)
Potrykus, A., A symbolic calculus and a parametrix construction for pseudodifferential operators with non-smooth negative definite symbols. Rev. Mat. Complut. 22 (2009), no. 1, 187--207.